Combinations of mediation and arbitration: The Singapore perspective - YIP, Man (Institutional Knowledge at Singapore Management University, 2021)
In recent years, Singapore has been actively rethinking and reworking ‘access to justice’, with a strong focus on creating new options for dispute resolution and promoting the awareness of these options. This chapter examines the judicial, regulatory and institutional support in Singapore for the twinning of mediation and arbitration as a form of multi-tier dispute resolution mechanism for commercial disputes. It is a hybrid approach that draws upon ‘the strengths of both adversarial and consensual dispute resolution’. In particular, this chapter critically analyses the SIMC-SIAC Arb-Med-Arb Protocol (the ‘AMA Protocol’) and interrogates how it contributes towards improving the arb-med-arb mechanism.